VD_FINDINFO Jug / 2014 / 381 vom 26. Juni 2014 - VD Tribunal cantonal (2014)
PEINE PRIVATIVE DE LIBERTÉ, FIXATION DE LA PEINE, RÉVOCATION DU SURSIS, PEINE COMPLÉMENTAIRE | 18 CP, 41 al. 1 CP, 41 ch. 1 CP, 41 ch. 2 CP, 46 al. 1 CP, 46 al. 2 CP, 47 al. 1 CP